Basics of inventory management : from warehouse to distribution centre - Viale, J. David (Crisp Pub. Menlo ParkUS, 1996)
Provides in-depth treatment of inventory management by explaining the major concepts, terms, definitions, tools, and techniques that comprise the inventory system. Explains how different business environments affect inventory management; how to identify and implement appropriate inventory systems.